A novel combination of nano-scaffolds with micro-scaffolds to mimic extracellularmatrices improve osteogenesis. (July 2014) - Xia, Yang; Peng, Sha-Sha; Xie, Li-Zhe; Lian, Xiao-Jie; Zhang, Xiao-Jun; Cui, Han; Song, Tian-Xi; Zhang, Fei-Min; Gu, Ning; Cui, Fu-Zhai
To improve bone engineering for clinical applications, we coupled nanofiber-peptide hydrogel to nano-hydroxyapatite/collagen to form a bioactive scaffold (cnHAC) that mimics extracellular matrices. In comparison to nano-hydroxyapatite/collagen, we found that cnHAC promoted cell adhesion and spreading, and DNA content measurements, alkaline phosphatase activity assays, and reverse transcriptase-polymerase chain reaction analyses of osteogenic gene expression showed that cnHAC significantly improved cellular attachment, proliferation, and osteogenic differentiation in vitro ( P  < 0.05). In vivo models based on rat calvarial implants showed that cnHAC significantly enhanced bone regeneration ( P  < 0.05). In conclusion, we demonstrated that novel cnHAC scaffolds could potentially facilitate future bone regenerative medicine.